2021
DOI: 10.3389/fcvm.2021.667554
|View full text |Cite
|
Sign up to set email alerts
|

Group A Streptococcus-Induced Activation of Human Plasminogen Is Required for Keratinocyte Wound Retraction and Rapid Clot Dissolution

Abstract: Invasive outcomes of Group A Streptococcus (GAS) infections that involve damage to skin and other tissues are initiated when these bacteria colonize and disseminate via an open wound to gain access to blood and deeper tissues. Two critical GAS virulence factors, Plasminogen-Associated M-Protein (PAM) and streptokinase (SK), work in concert to bind and activate host human plasminogen (hPg) in order to create a localized proteolytic environment that alters wound-site architecture. Using a wound scratch assay wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Here, we found that SprE actively degrades Pg and plasmin, suggesting that E. faecalis uses SprE to inactivate the fibrinolytic system. This strategy differs from other bacterial pathogens, including Group A Streptococcus (GAS), which activates Pg into plasmin via streptokinase, dissolving blood clot to cause an invasive infection 75 . Importantly, SprE specificity against Pg, Pm, and prekallikrein, suggests that SprE is recognizing a specific recognition site.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that SprE actively degrades Pg and plasmin, suggesting that E. faecalis uses SprE to inactivate the fibrinolytic system. This strategy differs from other bacterial pathogens, including Group A Streptococcus (GAS), which activates Pg into plasmin via streptokinase, dissolving blood clot to cause an invasive infection 75 . Importantly, SprE specificity against Pg, Pm, and prekallikrein, suggests that SprE is recognizing a specific recognition site.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that SprE actively degrades Pg and plasmin, suggesting that E. faecalis uses SprE to inactivate the fibrinolytic system. This strategy differs from other bacterial pathogens, including Group A Streptococcus (GAS), which activates Pg into plasmin via streptokinase, dissolving blood cloth to cause an invasive infection 66 . Therefore, identifying Pg/plasmin cleavage sites using purified SprE will be important to determine its action mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…clot and, consequently, the dissemination of bacterial cells [40]. It has also been de strated that binding of fibrinogen-or fibrin-degradation products to the M protein pyogenes protects bacterial cells from opsonization and phagocytosis [41].…”
Section: The Engagement Of Plasminogen and Plasmin In Infections-bene...mentioning
confidence: 99%